TGF Beta1 and TGF Beta2 and Their Role in Posthemorrhagic Hydrocephalus Following SAH and IVH - Kaestner, Stefanie; Dimitriou, Ioannis (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Objective Posthemorrhagic hydrocephalus (pHC) is a serious complication following subarachnoid hemorrhage (SAH) and intraventricular hemorrhage (IVH). Besides known clinical predictors, different cytokines have drawn attention to the development of chronic hydrocephalus. Transforming growth factor (TGF) β1 and TGF β2 are involved in fibrogenesis, scar formation, cell survival, and tissue differentiation and may play a role in the occurrence of pHC. TGF β1 is stored in platelets in large amount and is released in the cerebrospinal fluid (CSF) after SAH and IVH. Both TGF β1 and TGF β2 can be expressed by various intracranial cells.Methods TGF β1 and β2 were measured in CSF and blood samples of 42 patients with SAH or IVH with acute hydrocephalus during the first 10 days after ictus. Furthermore, albumin was measured in CSF as an indicator for the amount of blood. Patients were categorized as developing pHC requiring shunt treatment or not-developing pHC within 6 months.Results After adjusting for age, SAH resulted significantly more often in pHC than did IVH. Plasma levels of TGF β1 showed a marked increase over time, whereas CSF levels of TGF β1 constantly decreased. The time course of TGF β1 and albumin in CSF was paralleled and did not correlate with the development of shunt dependent pHC. Also, TGF β1 plasma concentrations did not correlate with shunt dependent pHC. TGF β2 concentrations in plasma showed stable values over time without any variations. TGF β2 in CSF described a parabolic course with a peak at day 6 after ictus. No correlation was found concerning TGF β2 in plasma or CSF and shunt dependent pHC.Conclusion TGF β1 in CSF is derived by platelets from the cisternal or ventricular clot. TGF β2 in CSF is derived as a general reaction of traumatized brain tissue. These data do not confirm a crucial role of TGF β1 and TGF β2 release in the development of pHC.
Keywords: TGF β1; TGF β2; subarachnoid hemorrhage; intraventricular hemorrhage; posthemorrhagic hydrocephalus